МАТЕРИАЛЫ ПО ВЫРАЩИВАНИЮ ВЕСЛОНОСА В ПОЛИКУЛЬТУРЕ C РУССКИМ ОСЕТРОМ (Eurasian Journal of Ecology, 2016)
Improved breeding Acipenseriformes biotechnology now allows juveniles to increase Poluodon spathula in pools over 3 g. This paper presents the experience of growing a large sample of young Poluodon spathula in polyculture with Acipenser gueldenstaedtii. Preliminary data on the cultivation of polycultures in industrial environments.